Pengaruh Electronic Word Of Mouth (E-WOM) Terhadap Minat Berkunjung Melalui Citra Destinasi Pada Wisata Taman Rekreasi Kota Bangkalan - Wahyuni, Sri; wantara, Pribanus (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
The development of the use of internet and social media is an oppurtunity for a tourist destination to increase the visitors. Likewise with TRK tour which is said still have minimal visitors, therefore there is a need information containing a special specification of TRK to triggers visit intention to make visit such as the destination image that is through EWOM. The purpose of this research was to find out how much influence EWOM has on visiting intention through destination image on Taman Rekreasi Kota in Bangkalan. This research using quantitative research with survey method via questionaire. The data analysis technique used to prove the hypothesis was compiled using Path Analysis and using the Sobel Test. The results of this research show that (1) EWOM has a direct, significant effect on visisting intentions; (2) EWOM has a direct effect on destination image; (3) The destination image has no effect on visiting interest and is not significant; (4) EWOM has limited indirect effect on visiting intention through the destination image, the destination image is able to mediate the effect between the Electronic Word Of Mouth on visiting intention. The researcher can conclude that the use of Electronic Word Of Mouth can influence the visiting intention and destination image is able to mediate it, but the mediating variable does not have much influence on the visiting intention.